PENDAMPINGAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN MINAT BELAJAR SISWA MA PONPES AL ISLAM - Sarah Caesarani; Anggun Tri Prabawati; Nina Nuryani; Alena Purnamasari; Fitri Fitri; Nurul Novianti; Muhamad Sunarya (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
One of the Field Experience Practices (PPL) service programs held at the Ma Ponpes Al Islam University of Bina Bangsa Academic Year 2022/2023 is information and communication technology socialization and training activities. The implementation of the Field Experience Practice (PPL) service program in the Ma Ponpes Al Islam environment aims to increase student interest in learning, in the development of information and communication technology so that the program can make Ma Ponpes Al Islam students more motivated in the world of information and communication technology. While the method of implementing the Field Experience Practice (PPL) service program includes information and communication technology education, motivation, and practice. The results of this PPL service activity are: 1) Increasing student interest in learning, 2) Increasing student knowledge and 3) increasing student motivation to learn Information and communication technology. Thus, the service carried out by the Bina Bangsa University Field Experience Practice Team (PPL) to the students of Ma Ponpes Al Islam in 2022 in information and communication technology socialization and training activities has been well realized.